2012
DOI: 10.1371/journal.pone.0033585
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 Oncoproteins Induce MMPs/RECK-TIMP-2 Imbalance in Primary Keratinocytes: Possible Implications in Cervical Carcinogenesis

Abstract: Cervical cancer is the third most common cancer in women worldwide. Persistent infection with high-risk HPV types, principally HPV16 and 18 is the main risk factor for the development of this malignancy. However, the onset of invasive tumor occurs many years after initial exposure in a minority of infected women. This suggests that other factors beyond viral infection are necessary for tumor establishment and progression. Tumor progression is characterized by an increase in secretion and activation of matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 40 publications
5
60
0
1
Order By: Relevance
“…In that model, the authors hypothesized that TIMP-2, but not RECK, is involved in MMP inhibition. However, in the present study, data from clinical samples evidenced an imbalance between MMP and RECK, which has already been shown in other human cancers (24)(25)(26) and in organotypic epithelial cultures with HPV-infected keratinocytes (11).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In that model, the authors hypothesized that TIMP-2, but not RECK, is involved in MMP inhibition. However, in the present study, data from clinical samples evidenced an imbalance between MMP and RECK, which has already been shown in other human cancers (24)(25)(26) and in organotypic epithelial cultures with HPV-infected keratinocytes (11).…”
Section: Discussionsupporting
confidence: 79%
“…To analyze MMPs status in a system that reproduces in vivo conditions, we have previously developed organotypic epithelial cultures with keratinocytes expressing HPV 16 oncoproteins. We have demonstrated that HPV 16 E7 induces pro-MMP-9 activity, and that E6 and E7 coexpression downregulates RECK protein levels (11). This latter study also demonstrated that, even in small number of clinical samples, there is an inverse correlation between RECK expression and degree of cervical lesion.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…MMPs, especially MMP2 and MMP9, are able to degrade ECM to promote endothelial cell migration and trigger an angiogenic switch by releasing VEGF from ECM (31). TIMPs are specific inhibitors of MMP2 and MMP9, which were decreased in CC (32,33). Our results revealed that TIMP2 abolished the stimulatory effect of miR-106a on CC cells.…”
Section: Discussionmentioning
confidence: 60%